A rational strategy to develop a boron nitride quantum dot-based molecular logic gate and fluorescent assay of alkaline phosphatase activity. Issue 6 (17th January 2019) - Han, Yaqian; Niu, Yusheng; Liu, Mengli; Niu, Fushang; Xu, Yuanhong
Abstract : By comparing the percentage of FL quenching and recovery of the BNQDs, a Fe 3+ -mediated FL quenching of BNQDs system was rationally designed for efficient ALP assay. Moreover, the aforementioned ensemble was exploited to newly construct a 2D-QD-based INH logic gate. Abstract : The metal-induced FL quenching of two-dimensional material-derived quantum dots (2D-QDs) has been playing vital roles in optical sensing recently; however, the metal type and concentration are usually chosen arbitrarily based on the maximum FL decrease although several metals may offer similar FL quenching effects towards the same 2D-QDs. Thus, a rational strategy was urgently needed to discover more efficient metal-mediated FL system for further applications. Taking boron nitride QDs (BNQDs) as a promising 2D-QD model, it was discovered that both Fe 3+ and Cu 2+ could quench their FL, which could be further switched on and off upon the addition of pyrophosphate and alkaline phosphatase, respectively. By comparing the percentage of FL quenching and recovery of BNQDs, it was rationally calculated that 300 μM Fe 3+ -mediated FL quenching of BNQDs paved a more efficient way for the sensitive and selective assay of ALP. Quantitative measurement of the ALP activity can be achieved with a low limit of detection of 0.8 U L −1 (S/N ≥ 3) in a wide range between 2 and 200 U L −1 . In addition, the aforementioned ensemble could be exploited to newly construct a 2D-QD-based "INH" logic gate. This approach possessed many superiorities i.e. low cost, simplicity, and high sensitivity.